Fundamentals of Electroheat Electrical Technologies for Process Heating - Lupi, Sergio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides a comprehensive overview of the main electrical technologies for process heating, which tend to be treated separately in specialized books. Individual chapters focus on heat transfer, electromagnetic fields in electro-technologies, arc furnaces, resistance furnaces, direct resistance heating, induction heating, and high-frequency and microwave heating. The authors highlight those topics of greatest relevance to a wide-ranging teaching program, and at the same time offer a detailed review of the main applications of the various technologies. The content represents a synthesis of the extensive knowledge and experience that the authors have accumulated while researching and teaching at the University of Padua's Engineering Faculty. This text on industrial electroheating technologies is a valuable resource not only for students of industrial, electrical, chemical, and material science engineering, but also for engineers, technicians and others involved in the application of electroheating and energy-efficient industrial processes.
Heat Transfer -- Electromagnetic fields in electro-technologies -- Arc Furnaces -- Direct Resistance Heating (DRH) -- Induction Heating -- High Frequency and Microwave Heating.
Keywords: Telecommunication; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Manufactures; Optical materials; Chemistry, Technical; Microwaves, RF Engineering and Optical Communications; Engineering Thermodynamics, Heat and Mass Transfer; Machines, Tools, Processes; Optical Materials; Industrial Chemistry